2013
DOI: 10.1080/1360080x.2013.844669
|View full text |Cite
|
Sign up to set email alerts
|

Shaping performance: do international accreditations and quality management really help?

Abstract: In recent years, international accreditations from private providers have gained importance among business schools all over the world. Higher education managers increasingly see these accreditations as a way of assuring and developing quality in order to comply with international standards, enhance performance, and increase reputation. However, given that an accreditation process requires a great deal of resources and that it might increase bureaucratization and control, international accreditations remain hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Accreditation systems are complex (Elliott, ; Francisco et al., ; Julian & Ofori‐Dankwa, ; Heriot et al., ; Nigsch & Schenker‐Wicki, ) and, if instituted, schools might need to change programs, curricula, admissions standards, staffing, administration, or facilities. Beyond that, ongoing efforts will be needed to sustain momentum for periodic review and reaccreditation (Elliott, ).…”
Section: Critical Perspectives On Accreditation: Applying Institutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accreditation systems are complex (Elliott, ; Francisco et al., ; Julian & Ofori‐Dankwa, ; Heriot et al., ; Nigsch & Schenker‐Wicki, ) and, if instituted, schools might need to change programs, curricula, admissions standards, staffing, administration, or facilities. Beyond that, ongoing efforts will be needed to sustain momentum for periodic review and reaccreditation (Elliott, ).…”
Section: Critical Perspectives On Accreditation: Applying Institutionmentioning
confidence: 99%
“…Navarro () in his survey of MBA curricula in U.S. business schools suggested that there was “a lack of emphasis on required multidisciplinary integration and experiential components” (p. 108). Nigsch and Schenker‐Wicki () observed that business accreditation changes in the 1990s reflected the wave of New Public Management (NPM) concepts entering academia. Harvey () in his study of higher education in Britain, the United States, and Canada noted that accreditation processes “are not benign or apolitical but represent a power struggle that impinges on academic freedom, while imposing an extensive bureaucratic burden in some cases” (p. 207).…”
Section: Critical Perspectives On Accreditation: Applying Institutionmentioning
confidence: 99%
See 3 more Smart Citations